Ribonucleotide reductase large subunit M1 predicts poor survival due to modulation of proliferative and invasive ability of gastric cancer. - Qinchuan Wang (Public Library of Science (PLoS), 2013)
Objectives We aimed to investigate the prognostic value of RRM1 in GC patients. Methods A total of assessable 389 GC patients with clinicopathological and survival information were enrolled from City of Hope (COH, n = 67) and Zhejiang University (ZJU, n = 322). RRM1 protein expression was determined by immunohistochemistry on FFPE tissue samples. Kaplan-Meier and Cox analyses were used to measure survival. Ras/Raf activity and invasion assays were used to evaluate the role of RRM1 in GC cell lines. Results In vitro experiments demonstrated RRM1 activated Ras/Raf/MAPK signal transduction and promoted GC cell proliferation. Meanwhile, RRM1 expression was significantly associated with lymph node involvement, tumor size, Ki67 expression, histological subtype and histological grade in the GC tissue samples (p<0.05). Kaplan-Meier analysis illustrated that high RRM1 expression predicted poor survival in GC patients in the COH and ZJU cohorts (log-rank p<0.01). In multivariate Cox analysis, the hazard ratios of RRM1 for overall survival were 2.55 (95% CI 1.27-5.15) and 1.51 (95% CI 1.07-2.13) in the COH and ZJU sets, respectively. In particular, RRM1 specifically predicted the outcome of advanced GCs with poor differentiation and high proliferative ability. Furthermore, inhibition of RRM1 by siRNA significantly reduced the dNTP pool, Ras/Raf and MMP-9 activities and the levels of p-MEK, p-ERK and NF-κB, resulting in growth retardation and reduced invasion in AGS and NCI-N87 cells. Conclusions RRM1 overexpression predicts poor survival in GC patients with advanced TNM stage. RRM1 could potentially serve as prognostic biomarker and therapeutic target for GCs.